2018
DOI: 10.1002/cctc.201801412
|View full text |Cite
|
Sign up to set email alerts
|

Restructured Fe−Mn Alloys Encapsulated by N‐doped Carbon Nanotube Catalysts Derived from Bimetallic MOF for Enhanced Oxygen Reduction Reaction

Abstract: A set of novel catalysts FeMn/N‐CNTs that partly maintain the core‐shell structure have been prepared successfully by calcination of analogous MOF‐74, which has bimetallic species (Fe and Mn) and a cheap organic ligand (2, 5‐dihydroxylbenzoic acid, DHBA) with melamine as additional nitrogen source. These catalysts exhibit a distinctive microstructure of Fe−Mn alloys surrounded by N‐doped carbon nanotubes (CNTs). Electrochemical methods have been employed to investigate their activity in oxygen reduction reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…When annealing with melamine, as displayed in Figure c, d and Figure S2, all samples of CoSMe‐X‐800 are shown as the structure of nanoparticle encapsulated into the nanotube, indicating that the nanotube are leaded by melamine pyrolysis. This statement is consistent with many previous reports about melamine pyrolysis and furthermore plentiful nitrogen atoms in melamine molecule are helpful to introduce the N species into as‐prepared carbon matrix, which can facilitate catalyzing ORR process.…”
Section: Resultssupporting
confidence: 92%
“…When annealing with melamine, as displayed in Figure c, d and Figure S2, all samples of CoSMe‐X‐800 are shown as the structure of nanoparticle encapsulated into the nanotube, indicating that the nanotube are leaded by melamine pyrolysis. This statement is consistent with many previous reports about melamine pyrolysis and furthermore plentiful nitrogen atoms in melamine molecule are helpful to introduce the N species into as‐prepared carbon matrix, which can facilitate catalyzing ORR process.…”
Section: Resultssupporting
confidence: 92%
“…Recently, nonprecious bimetallic materials (such as metal alloys), particularly, transition metal, have gained noticeable attention as candidates for oxygen electrocatalysts due to their highly active catalytic trait toward ORR and OER. An army of reported works has indicated that the bimetallic alloy catalysts display excellent electrocatalysis compared to their individual entity.…”
Section: Introductionmentioning
confidence: 99%
“…An MOF-74 precursor assembled from Fe/Mn and a cheap organic ligand (2,5-dihydroxyterephthalic acid) were combined with melamine and heated at 800 °C in a flow of N 2 to generate a core–shell catalyst denoted as Fe 3 Mn 1 /N-CNTs-100 [ 107 ]. SEM and TEM imaging showed that many 80-nm-diameter CNTs were formed during pyrolysis.…”
Section: Mof-based Orr Electrocatalystsmentioning
confidence: 99%